The role of cyclodextrin-tetrabutylammonium complexation on the cellulose dissolution. (20th April 2016) - Medronho, Bruno; Duarte, Hugo; Alves, Luis; Antunes, Filipe E.; Romano, Anabela; Valente, Artur J.M.
Highlights: The TBAH dissolution performance is affected by the presence of cyclodextrins. NMR titration experiments suggest the formation of 1:1 CD:TBA + complexes. β-CD has a stronger interaction with the TBAH solvent than α-CD. The presence of amphiphilic species in solution enhances cellulose solubility. Abstract: Cellulose dissolution is a challenging process which is typically very sensitive to the solvent characteristics such as pH, temperature or presence of additives. Regarding the later aspect, it is here reported the interaction between α-cyclodextrin (α-CD) and β-cyclodextrin (β-CD) with the tetrabutylammonium cation (TBA + ) by 1 H NMR titration experiments. The analysis by the continuous variation method suggests the formation of 1:1 CD:TBA + complexes. However, the computed apparent association constants reveal that the interaction of TBA + with the β-CD ( K  = 1580 M −1 ) is unexpectedly stronger than with α-CD ( K  = 106 M −1 ). In both CD cases, the formation of CD:TBA + complexes decrease the dissolution efficiency of the solvent and this has been rationalized as an effective decrease in the concentration of the amphiphilic cation and concomitant weakening of the hydrophobic interactions in solution influencing the overall performance of the solvent. Additionally, the data also supports the fact that amphiphilic species in solution are beneficial for the enhancement of cellulose solubility.